Investigations into Effect of By-product Binders in Improvement of Cyclic Behaviour of Soil - Keramatikerman, Mahdi (Curtin University, 2018)
This thesis investigates the effect of two by-product binders consisted of ground granulated blast furnace slag (GGBFS), and flyash (FA) on liquefaction resistance of soil by performing a comprehensive series of preliminary and core experimental studies. Also, a series of constitutive analysis have been performed based on the experimental studies to approximate the correlations of soil’s particle shape and binder contents with monotonic liquefaction. The results showed that they can improve liquefaction strength of soil.